Sexual Health in Adult Men with Spina Bifida - Gary W. Bong; Eric S. Rovner (The Scientific World Journal)
Medical and surgical advances in the treatment of spina bifida (SB) have resulted in increasing numbers of patients reaching adulthood. As such, issues related to sexual maturity are being investigated to offer optimal healthcare to men with spina bifida. This report constitutes a review of the current literature relating to adults with spina bifida and issues of sexuality, erectile dysfunction and fertility. In general, adult males with spina bifida have normal sexual desires and an interest in addressing these issues with healthcare providers. Sexual education and access to intimacy are delayed compared to the general population. 75% of men achieve erections, but maintaining erections is a problem and some may be merely reflexive in nature. The many of these men show marked improvement with sildenafil. In SB erectile dysfunction and infertility are related to the level of neurological lesion with the best performance status in those with sacral lesions and intact reflexes. Men with lesions higher than T10 are at risk for azoospermia. There is an increased risk of neural tube defects in the children of men with spina bifida, but the current incidence with modern folic acid therapy is unknown. As the number of males with spina bifida reaching sexual maturity increases, further investigation into sexuality, sex education, intimacy, and treatments for erectile dysfunction and infertility will be needed.